Repercussões psicossomáticas da hipnose em pessoas com diabetes Mellitus tipo 2 - Mateus, Rodrigo Cazarotto (2008)
This research is the result of the Master dissertation in Clinic Psychology at Hospital Psychology and Psychosomatic Nucleus from PUC-SP. The research aimed to check alteration on the glycemia level and on well-being sensation in people with Diabetes Mellitus type II after experiencing pleasure situations through the ericksonian hypnosis, as well as analyze the outcomes of the investigation. Ten subjects compounded the intervention group and eight subjects compounded the control group. Based on the literature revision, there were employed the following tools: socio-demographic questionnaire; semi-guided interview about pleasure situation; VAS Visual Analog Scale; glycemia level measurement and semi-guided interview about the intervention. The results were divided in five categories: socio-demographic data, pleasure experiences, glycemia level, well-being sensations and intervention perceptions. It was concluded that hypnosis helped decrease patients glycemia level after the last session, with a percentage reducing average of 13.20%, and the statement of every subject pointing out the improvement on the sensation of well-being after the intervention